1980
DOI: 10.1152/ajpendo.1980.239.5.e363
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent development of insulin resistance of soleus muscle in genetically obese (ob/ob) mice

Abstract: The relationship between insulin binding and its biological effects was studied in soleus muscle of 3- to 15-wk-old genetically obese (ob/ob) mice. At 3 and 4 wk of age, soleus muscle from lean and obese mice bound similar amounts of insulin under equilibrium binding conditions. However, by 6 wk of age, insulin binding and total receptor concentration (Ro) were significantly decreased in soleus muscle from obese compared to lean mice. In addition lean and obese mice demonstrated an age-dependent decrease in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
19
0
2

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
6
19
0
2
Order By: Relevance
“…1). These findings corroborate those of others made in other muscle types [4][5][6] and suggest that, although the heart is not representative of the muscle mass, it may undergo -upon the occurrence of insulin resistance -changes that are analogous to those seen in other muscles. This strengthens the observations made during the present study, with regard to the state of the glucose transporters as assessed by the cytochalasin B-binding assay.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…1). These findings corroborate those of others made in other muscle types [4][5][6] and suggest that, although the heart is not representative of the muscle mass, it may undergo -upon the occurrence of insulin resistance -changes that are analogous to those seen in other muscles. This strengthens the observations made during the present study, with regard to the state of the glucose transporters as assessed by the cytochalasin B-binding assay.…”
Section: Discussionsupporting
confidence: 89%
“…With regard to glucose uptake, it has been shown that basal, as well as insulin-stimulated glucose uptake, was decreased in most obesity syndromes studied [2,[4][5][6]. As is now well established in adipocytes [8,9] and also described in muscle [10], glucose transporting molecules (glucose transporters) are present both in the plasma and in some intracellular (microsomal) membranes.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Glucose tolerance and insulin sensitivity deteriorate with age in mice (Grundleger et al, 1980;Bailey and Flatt, 1982;Carvalho et al, 1996). Therefore, metabolic experiments should be carried out on agematched mice.…”
Section: Age and Sexmentioning
confidence: 99%
“…Adicionalmente, a resistência à insulina, por exemplo, é observada após a 3º-4º semana de vida (GRUNDLEGER et al, 1980). De fato, em nosso estudo, observamos que os animais com 12 semanas de vida apresentam maior intolerância à glicose, quando comparados aos animas com 4 semanas de vida.…”
Section: Vfc Representa Um Mau Prognóstico (Ribeiro and Moraes Filho 2unclassified